2019
DOI: 10.3389/fcvm.2019.00167
|View full text |Cite
|
Sign up to set email alerts
|

SS-31 Peptide Reverses the Mitochondrial Fragmentation Present in Fibroblasts From Patients With DCMA, a Mitochondrial Cardiomyopathy

Abstract: We used patient dermal fibroblasts to characterize the mitochondrial abnormalities associated with the dilated cardiomyopathy with ataxia syndrome (DCMA) and to study the effect of the mitochondrially-targeted peptide SS-31 as a potential novel therapeutic. DCMA is a rare and understudied autosomal recessive disorder thought to be related to Barth syndrome but caused by mutations in DNAJC19, a protein of unknown function localized to the mitochondria. The clinical disease is characterized by 3-methylglutaconic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
(47 reference statements)
2
31
0
Order By: Relevance
“…16 SS-31 has shown benefit in preclinical mitochondrial disorders and heart failure. 15,[17][18][19][20] We performed a randomized, double-blind, placebocontrolled crossover trial with an open-label extension to test the clinical efficacy and safety of daily administration of elamipretide in individuals with genetically confirmed Barth syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…16 SS-31 has shown benefit in preclinical mitochondrial disorders and heart failure. 15,[17][18][19][20] We performed a randomized, double-blind, placebocontrolled crossover trial with an open-label extension to test the clinical efficacy and safety of daily administration of elamipretide in individuals with genetically confirmed Barth syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…SS‐31 stabilizes the interaction between CL and ETC Complex II, thereby preventing cytochrome c release after exposure to oxidative stress. SS‐31 improves mitochondrial functioning and ameliorates oxidative damage in several disease models, including FRDA 27–31 . Certain biomarkers may be quantified to determine the effectiveness of drugs like SS‐31.…”
Section: Introductionmentioning
confidence: 99%
“…21 SS-31 has several advantages, including the ability to inhibit reperfusion injury and mitochondrial swelling, protection against mitochondrial depolarization and substantial scavenging of ROS. [22][23][24] The antioxidative effect of SS-31 in the eye has been reported in several studies. Chen and colleagues have shown that SS-31 can protect human trabecular meshwork cell lines induced by oxidative stress by inhibiting caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%